Genetic Adaptability of Sarotherodon Melanotheron to Polycyclic Aromatic Hydrocarbons (PAHs) in Some Senegal Hydrosystems - Yoboue, Ahou Nicole; Aliko, N’guessan Gustave; Gore, Bi Boh Nestor; Konan, Félix Koffi; Adepo-Gourene, Abouo Béatrice (European Scientific Journal, ESJ, 2018)
The objective of this study is to evaluate the level of Polycyclic Aromatic Hydrocarbons (PAH) contamination at the Sine-Saloum (Foundiougne, Kaolack and Missirah), Hann Bay and Niayes (1 and 2) sites in Sénégal and genetic ecotoxicology of Sarotherodon melanotheron specimens from these sites.The genes of the specimens were studied by the enzymatic electrophoresis technique. Seven enzymatic systems (ADH, AAT, IDHP, MDH, PGM, GPI and EST) were analyzed. The analysis of the PAHs was carried out by gas chromatography coupled to mass spectrometry (GCMS). Populations of Sarotherodon melanotheron and sediments used for PAH measurements were sampled in 2009. Chemical characterization of the sampling sites revealed a high concentration of PAHs at Foundiougne and Hann Bay. The high pollution of environment is characterized by PAH napht (Foundiougne (14 378 ng/g) ; Hann Bay (5856 ng/g). The analysis of allelic variability showed the existence of an adaptive polymorphism at the PGM locus in S. melanotheron. The particularly low frequencies of the PGM * 105 allele in populations of disturbed environment (Foundiougne, Kaolack, Hann Bay, Niayes 1 and Niayes 2) suggest its involvement in the response to environmental stress. A negative correlation was observed between the PGM, IDHP and MDH-1 locus and PAH. The presence of PAHs in the environmentcauses to a decrease in the frequency of the PGM * 105 alleleatS. melanotheronspecimens.